Digital literacy training for female employees at CV Gemilang Kencana - Adiana, Beta Estri; Mareta, Affix; Fathony, Ikhwan Alfath Nurul; Wardhani, Olivia (Community Empowerment, 2025)
CV Gemilang Kencana, a Micro, Small, and Medium-sized Enterprise (MSME) in the food and beverage processing sector in Wonosobo Regency, faces challenges in leveraging digital technology due to low digital literacy among its employees, particularly women. This community service initiative aimed to enhance the digital literacy skills of female employees through training that covered basic technology introduction, productivity application usage, and the utilization of social media for product marketing. The implementation method involved preparation, training delivery, and evaluation stages. The training results demonstrated a significant improvement in participants' digital understanding and skills, with the average pre-test score of 46.5% increasing to 81% post-training. Active participants were able to independently utilize social media for product marketing and contributed to improved operational efficiency and MSME competitiveness. This training proved effective in empowering women and supporting digital transformation within the MSME sector, while also enhancing participants' capabilities in navigating the increasingly digitalized era.